The relationship of self-efficacy and academic performance among male and female UPVTC junior college students. - Esperancilla, Glaiza O.; Moral, Joselle O. (Glaiza O. Esperancilla and Joselle O. Moral, 2007)
This study was made to investigate the relationship between the level of self-efficacy and academic performance. Specifically, it drew up the respondents performance and sex, looked into whether a significant difference existed between the level of self-efficacy of the high achievers, determined the significant difference in the level of self-efficacy of males and females. The descriptive-correlational method was utilized in this study. The research study was conducted in the University of the Philippines in the Visayas Tacloban College during the school year 2006-2007. The population of this study was limited to Third Year students only. The sampling technique used was stratified random sampling and the sample comprised 100 students. Data on the level of self-efficacy of the respondents were gathered using the Self-Inventory Test for Self-efficacy of College Students. The academic performance of the respondents was measured by their GWA in the first year to third year of first semester. Data were presented, analyzed and interpreted through the use of the mean, frequency counts and percentages, Pearson's Product Moment Correlation and two t-tests. Results revealed that most of the respondents have high level of self-efficacy. There was a moderate correlation between level of self-efficacy and academic performance (r= -0.58). This correlation was found to be significant at 0.05 level of significance. These implied that the two variables do not always go together. A significant difference was found to exist in the level of self-efficacy of high achievers and low achievers (t obs = 5.707). However, no significant difference was found in males and females (t obs = 0.10). This inferred that self-efficacy beliefs are more or less similar regardless of their sex. It is therefore recommended that self-efficacy beliefs be developed and enhanced among the students to help improve the academic performance of the students. In addition, factors such as age differences and difference between males and females in different dimensions of self-efficacy beliefs are managed to be considered in further studies.